Mirror mirror on my pen struggle, identity and the compensation of loneliness in the autobıographical narratives of Middle Eastern women writers in exile - Ömür, Dilara (İstanbul Bilgi Üniversitesi, 2017)
[Abstract Not Available]
Ayna ayna, yaz beni: Orta Doğulu sürgün kadın yazarların otobiyografik anlatılarında yalnızlığın telafisi, mücadele ve kimlik